Vanadium-titanium-zirconium composite modified nanometer niobium carbide material and preparation method thereof
The preparation method of vanadium-titanium-zirconium composite modified niobium carbide nanomaterials solves the problems of low purity, large grain size, high impurities and low hardness of existing niobium carbide materials. It produces high-purity, fine-grained niobium carbide nanomaterials, which meet the application needs of cemented carbide and high-end fields, and has the potential for industrial production.
Patent Information
- Application Number
- CN202611446334.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-11-03
AI Technical Summary
Existing niobium carbide materials have low purity, large grains, high impurities, and low hardness, making it difficult to meet the preparation requirements of cemented carbide and high-end fields.
A method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials was adopted. The niobium source, vanadium powder, titanium powder and zirconium powder were mixed and then ball-milled, sieved and vacuum calcined to prepare niobium carbide nanomaterials with high purity, small particle size and uniform particle distribution.
The prepared nano-niobium carbide material has a purity of ≥95.0wt%, an average grain size of <100nm, an oxygen impurity content of ≤0.15wt%, and improved hardness. It is suitable for ultrafine cemented carbide and high-end applications. Moreover, the preparation method is simple, the raw materials are cheap and readily available, and it is suitable for large-scale industrial production.
Smart Images

Figure CN123027469A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials technology, specifically relating to a vanadium-titanium-zirconium composite modified nano-niobium carbide material and its preparation method. Background Technology
[0002] Niobium carbide (NbC) possesses excellent thermal stability, hardness, and corrosion resistance, playing a crucial role in the preparation of cermets, heat-resistant alloys, and cemented carbides. As an additive, it can significantly improve the hot hardness, thermal shock resistance, and oxidation resistance of cemented carbides. Multiphase materials made from NbC are widely used in high-end fields such as fusion reactors, machining, metallurgy, and aerospace, and market demand continues to rise.
[0003] Currently, the mainstream preparation methods for niobium carbide include the carbothermal reduction of niobium pentoxide, the metal niobium carbide method, and the chemical vapor phase reaction method. Among them, the carbothermal reduction of niobium pentoxide has become the main application technology in China due to its relatively mature process, but it has the following problems: it requires two high-temperature reduction treatments, making the process complex and extremely energy-intensive; poor uniformity of raw material mixing leads to incomplete reaction, and residual impurities affect product purity; the decarburization process requires high-temperature conditions, further increasing the oxygen content and reducing product quality. Other preparation methods either have stringent equipment requirements or insufficient product stability, making it difficult to meet the needs of industrial production.
[0004] With the rapid development of the cemented carbide industry, the performance requirements for niobium carbide are becoming increasingly stringent, with ultrafine particle size (e.g., Fsss ≤ 1.3 μm) and low impurity content becoming the mainstream market demand. However, existing domestic preparation processes generally produce niobium carbide with large particle sizes, which cannot meet the preparation standards of high-end cemented carbide, thus hindering the upgrading and development of related industries. Therefore, developing a low-energy-consumption, low-cost preparation technology that can stably produce ultrafine niobium carbide has become a key issue that the industry urgently needs to address.
[0005] In view of this, it is necessary to provide a vanadium-titanium-zirconium composite modified nano-niobium carbide material and its preparation method to overcome the shortcomings of the existing technology. Summary of the Invention
[0006] The purpose of this invention is to provide a vanadium-titanium-zirconium composite modified nano-niobium carbide material and its preparation method, which solves the problems of low purity, large grain size, high impurities, and low hardness of existing niobium carbide materials.
[0007] In a first aspect, the present invention provides a method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials, comprising the following steps: mixing niobium source, reducing agent, vanadium powder, titanium powder, and zirconium powder uniformly to obtain a mixture; subjecting the mixture to ball milling and sieving in sequence to obtain a composite powder; subjecting the composite powder to vacuum calcination and cooling to room temperature under vacuum conditions to obtain vanadium-titanium-zirconium composite modified niobium carbide nanomaterials; wherein, in the step of obtaining the mixture, the mass ratio of niobium source to reducing agent is 1:(0.25~0.4), and the reducing agent includes carbon black.
[0008] In this invention, the inventors discovered that by adding vanadium powder, titanium powder, zirconium powder, etc. as modifiers, and then combining them with specific ball milling, sieving, and vacuum calcination processes, a vanadium-titanium-zirconium composite modified niobium carbide nanomaterial with high purity, small particle size, uniform particle distribution, and no obvious agglomeration or blocky impurities can be prepared. This material can meet the needs of ultrafine cemented carbide preparation and high-end applications. In addition, the preparation method provided by this invention is simple, and the raw materials used are inexpensive and readily available, making it suitable for large-scale industrial production and application, and it has good application prospects.
[0009] In some embodiments, in the step of obtaining the mixture, the niobium source comprises niobium hydroxide, and the particle size of the niobium hydroxide is less than 1.0 μm.
[0010] In some implementations, in the step of obtaining the mixture, the amount of vanadium powder added is 0.10 to 0.20 wt% of the total mass of the niobium source and reducing agent.
[0011] In some implementations, in the step of obtaining the mixture, the amount of titanium powder added is 0.05 to 0.15 wt% of the total mass of the niobium source and reducing agent.
[0012] In some implementations, in the step of obtaining the mixture, the amount of zirconium powder added is 0.05 to 0.10 wt% of the total mass of the niobium source and reducing agent.
[0013] In some implementations, the ball milling process in the step of obtaining the composite powder specifically includes: controlling the ball-to-material ratio to be 1:(0.8~2), the rotation speed to be 200~800 rpm, and the ball milling time to be 5~20 h.
[0014] In some implementations, the sieving process in the step of obtaining the composite powder specifically includes sieving with a sieve aperture of 124~150μm.
[0015] In some implementation schemes, the vacuum calcination process in obtaining vanadium-titanium-zirconium composite modified niobium carbide nanomaterials specifically includes: holding at a temperature of 1000~1500℃ for 1~10 hours under a pressure of less than 0.04 MPa.
[0016] Secondly, the present invention provides a vanadium-titanium-zirconium composite modified niobium carbide nanomaterial, which is prepared by any of the above preparation methods.
[0017] In some implementation schemes, the purity of the vanadium-titanium-zirconium composite modified nano-niobium carbide material is ≥95.0wt%, the average grain size is <100nm, and the oxygen impurity content is ≤0.15wt%.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials provided by this invention involves adding vanadium powder, titanium powder, zirconium powder, etc. as modifiers, followed by specific ball milling, sieving, and vacuum calcination treatments. The resulting niobium carbide nanomaterials have high purity, small particle size, uniform particle distribution, and no obvious agglomeration or blocky impurities, which can meet the needs of ultrafine cemented carbide preparation and high-end applications. In addition, the preparation method provided by this invention is simple, and the raw materials used are inexpensive and readily available, making it suitable for large-scale industrial production and application, and has good application prospects. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation method of the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial in this invention. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having”, and any variations thereof, in the specification and claims of this invention are intended to cover non-exclusive inclusion.
[0022] In the description of the embodiments of this invention, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this invention, "multiple" means two or more, unless otherwise explicitly defined.
[0023] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0024] In the description of the embodiments of the present invention, the term "and / or" is merely a description of the relationship between associated objects, indicating that there can be three relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone.
[0025] Experimental methods not specified in the examples are generally performed under conventional conditions and as described in the manual, or as recommended by the manufacturer. Unless otherwise specified, the general equipment, materials, reagents, etc. used are commercially available.
[0026] Currently, existing niobium carbide materials suffer from problems such as low purity, large grain size, high impurity content, and low hardness.
[0027] To address the problems of low purity, large grain size, high impurities, and low hardness in existing niobium carbide materials, this invention provides a vanadium-titanium-zirconium composite modified nano-niobium carbide material and its preparation method.
[0028] In a first aspect, the present invention provides a method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials, comprising the following steps: mixing niobium source, reducing agent, vanadium powder, titanium powder, and zirconium powder uniformly to obtain a mixture; subjecting the mixture to ball milling and sieving in sequence to obtain a composite powder; subjecting the composite powder to vacuum calcination and cooling to room temperature under vacuum conditions to obtain vanadium-titanium-zirconium composite modified niobium carbide nanomaterials; wherein, in the step of obtaining the mixture, the mass ratio of niobium source to reducing agent is 1:(0.25~0.4), and the reducing agent includes carbon black.
[0029] The preparation method provided by this invention involves adding vanadium powder, titanium powder, zirconium powder, etc. as modifiers, followed by specific ball milling, sieving, and vacuum calcination treatments. This process yields vanadium-titanium-zirconium composite modified niobium carbide nanomaterials with high purity, small particle size, uniform particle distribution, and no obvious agglomeration or blocky impurities. These materials meet the requirements for ultrafine cemented carbide preparation and high-end applications. Furthermore, the preparation method provided by this invention is simple, and the raw materials used are inexpensive and readily available, making it suitable for large-scale industrial production. Therefore, it has promising application prospects.
[0030] In some embodiments, in the step of obtaining the mixture, the niobium source comprises niobium hydroxide, and the particle size of the niobium hydroxide is less than 1.0 μm.
[0031] In this invention, by controlling the particle size of niobium hydroxide within a specific range, it is easier to efficiently dope with subsequent modifiers, thereby significantly improving the performance of vanadium-titanium-zirconium composite modified nano-niobium carbide materials.
[0032] In some embodiments, in the step of obtaining the mixture, the amount of vanadium powder added is 0.10 to 0.20 wt% of the total mass of the niobium source and reducing agent, for example, it can be 0.10 wt%, 0.12 wt%, 0.14 wt%, 0.16 wt%, 0.18 wt%, 0.20 wt%, or other values within this range.
[0033] In this invention, by controlling the amount of vanadium powder added within a specific range, the vanadium powder can be uniformly dispersed in the vanadium-titanium-zirconium composite modified nano-niobium carbide material, thereby significantly improving the performance of the vanadium-titanium-zirconium composite modified nano-niobium carbide material.
[0034] In some embodiments, in the step of obtaining the mixture, the amount of titanium powder added is 0.05 to 0.15 wt% of the total mass of the niobium source and reducing agent, for example, it can be 0.05 wt%, 0.07 wt%, 0.10 wt%, 0.13 wt%, 0.15 wt%, or other values within this range.
[0035] In this invention, by controlling the amount of titanium powder added within a specific range, the titanium powder can be uniformly dispersed in the vanadium-titanium-zirconium composite modified nano-niobium carbide material, thereby significantly improving the performance of the vanadium-titanium-zirconium composite modified nano-niobium carbide material.
[0036] In some embodiments, in the step of obtaining the mixture, the amount of zirconium powder added is 0.05 to 0.10 wt% of the total mass of the niobium source and reducing agent, for example, it can be 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, 0.10 wt% or other values within this range.
[0037] In this invention, by controlling the amount of zirconium powder added within a specific range, the zirconium powder can be uniformly dispersed in the vanadium-titanium-zirconium composite modified nano-niobium carbide material, thereby significantly improving the performance of the vanadium-titanium-zirconium composite modified nano-niobium carbide material.
[0038] In some embodiments, the ball milling process in obtaining the composite powder specifically includes: controlling the ball-to-powder ratio to be 1:(0.8~2), for example, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or other ratios within this range; the rotation speed to be 200~800 rpm, for example, 200 rpm, 400 rpm, 600 rpm, 800 rpm or other values within this range; and the ball milling time to be 5~20 h, for example, 5 h, 10 h, 15 h, 20 h or other values within this range.
[0039] In this invention, by controlling the parameters of ball milling within a specific range, the raw materials can be fully mixed and activated, facilitating subsequent reactions.
[0040] In some embodiments, the sieving process in the step of obtaining the composite powder specifically includes: sieving with a pore size of 124~150μm, for example, 124μm, 130μm, 140μm, 150μm or other values within this range.
[0041] In this invention, sieving facilitates efficient subsequent reactions of the materials.
[0042] In some embodiments, the vacuum calcination treatment in the step of obtaining vanadium-titanium-zirconium composite modified niobium carbide nanomaterials specifically includes: holding at a pressure of less than 0.04 MPa and a temperature of 1000~1500℃ (e.g., 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃ or other values within this range) for 1~10 h, e.g., 1 h, 3 h, 5 h, 7 h, 10 h or other values within this range.
[0043] In this invention, by controlling the parameters of vacuum calcination within a specific range, the reaction can be made completely, thereby significantly improving the performance of vanadium-titanium-zirconium composite modified nano-niobium carbide materials; at the same time, the reaction temperature and time are greatly reduced, energy consumption is significantly reduced, and product quality is ensured to be stable and controllable.
[0044] Secondly, the present invention provides a vanadium-titanium-zirconium composite modified niobium carbide nanomaterial, which is prepared by any of the above preparation methods.
[0045] In some implementation schemes, the purity of the vanadium-titanium-zirconium composite modified nano-niobium carbide material is ≥95.0wt%, the average grain size is <100nm, and the oxygen impurity content is ≤0.15wt%.
[0046] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0047] Please see Figure 1 The flowchart illustrates the preparation method of the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial in this invention. Specifically, the preparation method includes the following steps: mixing niobium source, reducing agent, vanadium powder, titanium powder, and zirconium powder uniformly to obtain a mixture; subjecting the mixture to ball milling and sieving processes sequentially to obtain a composite powder; subjecting the composite powder to vacuum calcination and cooling it to room temperature under vacuum conditions to obtain the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial.
[0048] Example 1 A method for preparing a vanadium-titanium-zirconium composite modified niobium carbide nanomaterial includes the following steps: S1. Accurately weigh 10g of niobium hydroxide (Nb(OH)5) with a particle size of 0.8μm, 3g of carbon black, 0.015g of vanadium powder, 0.008g of titanium powder, and 0.007g of zirconium powder, and then mix them evenly to obtain a mixture. S2. The mixture obtained in step S1 is put into a planetary ball mill for dry grinding. The ball-to-material ratio is controlled at 1:1, the rotation speed is 400 rpm, and the ball milling time is 8 hours. After the ball milling is completed, the mixture is passed through a 150 μm sieve to obtain composite powder. S3. The composite powder obtained in step S2 is loaded into a graphite crucible and placed in a vacuum well furnace. The furnace pressure is maintained at 0.03 MPa and the temperature at 1100℃ for 1.5 h. After sintering, the furnace is cooled to room temperature under vacuum conditions to obtain vanadium-titanium-zirconium composite modified nano-niobium carbide material.
[0049] Example 2 A method for preparing a vanadium-titanium-zirconium composite modified niobium carbide nanomaterial includes the following steps: S1. Accurately weigh 40g of niobium hydroxide (Nb(OH)5) with a particle size of 0.6μm, 13g of carbon black, 0.06g of vanadium powder, 0.04g of titanium powder, and 0.03g of zirconium powder, and then mix them evenly to obtain a mixture. S2. The mixture obtained in step S1 is put into a planetary ball mill for dry grinding. The ball-to-material ratio is controlled at 1:1.5, the rotation speed is 600 rpm, and the ball milling time is 12 h. After the ball milling is completed, it is passed through a 150 μm sieve to obtain composite powder. S3. The composite powder obtained in step S2 is loaded into a graphite crucible and placed in a vacuum well furnace. The furnace pressure is maintained at 0.02 MPa and the temperature at 1250 °C for 3 hours. After sintering, the furnace is cooled to room temperature under vacuum conditions to obtain vanadium-titanium-zirconium composite modified nano-niobium carbide material.
[0050] Comparative Example 1 In this comparative example, the preparation method of the nano-niobium carbide material is basically the same as that in Example 2. The difference is that vanadium powder, titanium powder, and zirconium powder are not added in step S1.
[0051] Comparative Example 2 In this comparative example, the preparation method of the modified nano-niobium carbide material is basically the same as that in Example 2. The difference is that vanadium powder and titanium powder are not added in step S1.
[0052] Comparative Example 3 In this comparative example, the preparation method of the modified nano-niobium carbide material is basically the same as that in Example 2. The difference is that vanadium powder and zirconium powder are not added in step S1.
[0053] Comparative Example 4 In this comparative example, the preparation method of the modified nano-niobium carbide material is basically the same as that in Example 2. The difference is that in step S1, titanium powder and zirconium powder are not added.
[0054] Comparative Example 5 In this comparative example, the preparation method of the modified nano-niobium carbide material is basically the same as that in Example 2, except that vanadium powder is not added in step S1.
[0055] Comparative Example 6 In this comparative example, the preparation method of the modified nano-niobium carbide material is basically the same as that in Example 2, except that titanium powder is not added in step S1.
[0056] Comparative Example 7 In this comparative example, the preparation method of the modified nano-niobium carbide material is basically the same as that in Example 2, except that zirconium powder is not added in step S1.
[0057] Performance testing For example, the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial prepared in Example 2 was characterized by SEM-EDS. The microstructure of the material observed by scanning electron microscopy showed that the product particles were small, without obvious large agglomerations, and the particle size distribution was uniform, with no blocky impurities observed. EDS elemental distribution analysis was used to detect the elemental distribution within the material. The results showed that vanadium, titanium, and zirconium were uniformly dispersed within the niobium carbide matrix, without local element enrichment or agglomeration, achieving effective composite doping of the three modifying elements in the niobium carbide matrix.
[0058] Furthermore, the performance of the vanadium-titanium-zirconium composite modified niobium carbide nanomaterials prepared in Examples 1-2, the niobium carbide nanomaterials prepared in Comparative Example 1, and the modified niobium carbide nanomaterials prepared in Comparative Examples 2-7 were tested, and the results are shown in Table 1 below.
[0059] Table 1 Performance Test Results
[0060] As can be seen from Table 1, in Examples 1 and 2, the three modifying components of vanadium powder, titanium powder and zirconium powder were compounded simultaneously. The resulting nano-niobium carbide products had a purity greater than 95wt%, an average grain size less than 100nm, an oxygen impurity content ≤0.15wt%, and a significantly higher Vickers hardness. All indicators met the expectations of this invention.
[0061] In Comparative Example 1, no vanadium, titanium, or zirconium modifiers were added. The niobium carbide grains grew significantly to 186 nm, and the oxygen impurity content was as high as 0.31 wt%. The product purity decreased and the hardness was significantly lower.
[0062] Comparative Examples 2-7 are control groups lacking any one or two modifying elements. When only one or two modifying components are added, although the performance of the obtained nano-niobium carbide is improved compared with that of the nano-niobium carbide obtained in Comparative Example 1, the effect of inhibiting grain growth and deoxidation purification is limited. The average grain size is greater than 100 nm, the oxygen impurity content is higher than 0.15 wt%, and the purity and hardness are not as good as those of Examples 1 and 2 of this invention.
[0063] The above results indicate that only synergistic composite modification with vanadium, titanium, and zirconium can achieve multiple effects, including grain boundary pinning to inhibit grain growth, deoxidation and impurity removal under vacuum, and activation of the carbonization reaction in niobium carbide. Combining a single or two modifying elements makes it difficult to simultaneously achieve the comprehensive properties of low oxygen content, fine nanocrystals, and high purity in niobium carbide. The VC, TiC, and ZrC dispersed phases formed by V-Ti-Zr ternary modification can cover the entire calcination temperature range of 1000-1500℃, avoiding the failure of pinning effects of a single inhibitor at high temperatures. Simultaneously, the strong deoxidation effect of V, Ti, and Zr can effectively remove residual oxygen impurities from the system, improving the purity of niobium carbide, and the dispersion strengthening effect further enhances the hardness of the nano-niobium carbide material.
[0064] In summary, the preparation method of vanadium-titanium-zirconium composite modified niobium carbide nanomaterials provided in this invention, by adding vanadium powder, titanium powder, zirconium powder, etc. as modifiers, has the following advantages: 1) Grain growth inhibition (core function): At high temperature, nano-VC, TiC and ZrC dispersed phases are generated to pin NbC grain boundaries, hindering grain boundary migration and atomic diffusion. The ternary composition covers the entire sintering range of 1000~1500℃, avoiding the failure of single inhibitors at high temperature, and stably controlling the grain size within 100nm.
[0065] 2) Deoxygenation and purification: V, Ti, and Zr have a much stronger ability to combine with oxygen than niobium. They preferentially capture residual oxygen and free oxygen in the system by decomposing niobium hydroxide, generating volatile oxides that are discharged with vacuum, significantly reducing the oxygen content of the finished product and improving the purity of NbC.
[0066] 3) Activation of carbonization reaction: Trace amounts of V, Ti, and Zr are dissolved into the NbC lattice to form a composite carbide solid solution, which distorts the crystal structure, enhances the reaction activity, lowers the lower limit of the carbonization reaction temperature, shortens the holding time, and reduces energy consumption.
[0067] 4) Enhanced terminal performance: The uniformly distributed nano-VC / TiC / ZrC second phase in the matrix produces a dispersion strengthening effect, which improves the hardness, high-temperature oxidation resistance and thermal shock resistance of niobium carbide powder itself. When added to cemented carbide, it greatly improves the service life of cutting tools and high-temperature components.
[0068] It should be noted that all the above embodiments belong to the same inventive concept, and the descriptions of each embodiment have different focuses. Where the description in a particular embodiment is not detailed, please refer to the description in other embodiments.
[0069] The embodiments described above are merely illustrative of implementation methods of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a vanadium-titanium-zirconium composite modified niobium carbide nanomaterial, characterized in that, Includes the following steps: The niobium source, reducing agent, vanadium powder, titanium powder, and zirconium powder are mixed evenly to obtain a mixture. The mixture was subjected to ball milling and sieving processes in sequence to obtain composite powder. The composite powder was subjected to vacuum calcination and then cooled to room temperature under vacuum conditions to obtain the vanadium-titanium-zirconium composite modified nano-niobium carbide material. In the step of obtaining the mixture, the mass ratio of the niobium source to the reducing agent is 1:(0.25~0.4), and the reducing agent includes carbon black.
2. The preparation method of the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial according to claim 1, characterized in that, In the step of obtaining the mixture, the niobium source comprises niobium hydroxide, and the particle size of the niobium hydroxide is less than 1.0 μm.
3. The preparation method of the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial according to claim 1, characterized in that, In the step of obtaining the mixture, the amount of vanadium powder added accounts for 0.10~0.20 wt% of the total mass of the niobium source and reducing agent.
4. The method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials according to claim 1, characterized in that, In the step of obtaining the mixture, the amount of titanium powder added accounts for 0.05~0.15 wt% of the total mass of the niobium source and reducing agent.
5. The preparation method of the vanadium-titanium-zirconium composite modified niobium carbide nanomaterial according to claim 1, characterized in that, In the step of obtaining the mixture, the amount of zirconium powder added accounts for 0.05~0.10 wt% of the total mass of the niobium source and reducing agent.
6. The method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials according to claim 1, characterized in that, In the step of obtaining the composite powder, the ball milling process specifically includes: controlling the ball-to-material ratio to be 1:(0.8~2), the rotation speed to be 200~800 rpm, and the ball milling time to be 5~20 h.
7. The method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials according to claim 1, characterized in that, In the step of obtaining the composite powder, the sieving process specifically includes: the sieve aperture is 124~150μm.
8. The method for preparing vanadium-titanium-zirconium composite modified niobium carbide nanomaterials according to claim 1, characterized in that, In the step of obtaining the vanadium-titanium-zirconium composite modified nano-niobium carbide material, the vacuum calcination treatment specifically includes: holding at a temperature of 1000~1500℃ for 1~10 hours under a pressure of less than 0.04 MPa.
9. A vanadium-titanium-zirconium composite modified niobium carbide nanomaterial, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. The vanadium-titanium-zirconium composite modified niobium carbide nanomaterial according to claim 9, characterized in that, The vanadium-titanium-zirconium composite modified nano-niobium carbide material has a purity ≥95.0wt%, an average grain size <100nm, and an oxygen impurity content ≤0.15wt%.
